ESTUDO IMUNOFENOTÍPICO DAS LEUCEMIAS AGUDAS NO CENTRO ONCOLÓGICO DE REFERÊNCIA DO ESTADO DO MARANHÃO - Noronha, Elda Pereira (2010)
Acute leukaemia is the most common type of cancer in childhood. Its diagnosis depends on immunophenotyping, which enables identification of the lineage, the grade of maturation, and the identification of markers with prognostic value. Assessment of the incidence of leukaemia subtypes worldwide has shown important variations in relation to geographical distribution, sex, age, ethnicity and socio-economic conditions. The objective of this work was to determine the immunophenotypic profile and the frequency, in different age groups, of subtypes of acute leukaemia in patients treated at the oncology center of reference Instituto Maranhense de Oncologia Aldenora Bello, in São Luís, Maranhão, and to study, in children with acute lymphoid leukaemia (ALL), the relationship between the expression of CD34 and the expression of aberrant phenotypes and prognostic factors. The diagnosis of acute leukaemia was obtained based on blood count, myelograms, cytochemical tests and immunophenotyping by flow cytometry. Monoclonal antibodies were used against T antigens (CD1a, CD2, CD3, CD4, CD5, CD7 and CD8), B antigens (CD10, CD19, CD22, CD79a and IgM), antigens of myeloid (CD13, CD14, CD33, CD64, CD117, MPO), erythroid (alpha-glycophorin), and platelet (CD61 and CD41a) differentiation, non-specific lineage antigen (CD45) and precursor cell antigens (CD34, HLA-DR). Acute leukaemia was classified according to the French-American-British (FAB) classification criteria and those of the European Group for the Immunological Characterisation of Leukaemias (EGIL). Seventy cases of de novo acute leukaemias were analysed over the period from September 2008 to January 2010, of which 31.4% were in adults and 68.6% in children. Among the adult patients 22.7% were diagnosed with ALL and 77.3% with acute myeloid leukaemia (AML), with the AML M0 subtype being most frequent. In children, 77.1% of the patients were diagnosed with ALL, and 18.7% with AML, with the AML M4 subtype the most frequent, and 4.2% with acute biphenotypic leukaemia (ABL). Among ALL, in children, B-ALL represented 72.9% of the cases and T-ALL 27.1%. The peak incidence of ALL was between 1 and 4 years of age. The most frequent subtypes of B-ALL were BII-ALL (pre-pre-B, common B), followed by the subtype BIII-ALL (pre-B). Among ALL and AML there was anomalous expression in 45.2% and 26.9% of cases, respectively. In ALL among children no statistically significant difference was found between the groups with and without anomalous expression in relation to the haematological parameters and the response to treatment. The expression of CD34 was negatively correlated with the number of leucocytes and percentage of blasts in peripheral blood. Furthermore, the expression of CD34 in B-ALL appeared to be associated with characteristics of better prognosis, while in T-ALL the opposite was observed. The antibodies used were sufficient to classify the cases immunologically. The use of immunophenotyping to diagnose acute leukaemias in our state enabled the diagnosis of minimally differentiated cases of AML (AML M0), as well as detection of the increased frequency of T-ALL in our population, suggesting that there may be differences in the prevalence of the FAB subtypes of AML, as well as the subtypes of ALL, in different regions of Brazil.